The Path to Universal Health Coverage in Bangladesh : Bridging the Gap of Human Resources for Health - El-Saharty, Sameh (Washington, DC: World Bank, 2015)
Bangladesh is committed to achieving universal health coverage (UHC) by 2032; to this end, the government of Bangladesh is exploring policy options to increase fiscal space for health and expand coverage while improving service quality and availability. Despite Bangladesh’s impressive strides in improving its economic and social development outcomes, the government still confronts health financing and service delivery challenges.